Novel method utilizing bisulfite conversion with dual amplification‐refractory mutation system polymerase chain reaction to detect circulating pancreatic β‐cell cfDNA. Issue 7 (6th May 2022) - Okada, Asami; Yamada‐Yamashita, Misuzu; Tominaga, Yukari; Jo, Kyoka; Mori, Hiroyasu; Suzuki, Reiko; Ishizu, Masashi; Tamaki, Motoyuki; Akehi, Yuko; Takashi, Yuichi; Koga, Daisuke; Shimokita, Eisuke; et al.
Abstract: Aims/Introduction: Several research groups have reported methods for quantifying pancreatic beta cell (β‐cell) injury by measuring β‐cell‐specific CpG unmethylation of the insulin gene in circulation using digital droplet PCR or next‐generation sequencing. However, these methods have certain disadvantages, such as the need to consider the background signal owing to the small number of target CpG sites and the need for unique equipment. Materials and Methods: We established a novel method for detecting four CpG unmethylations of the insulin gene using two‐step amplification refractory mutation system PCR. We applied it to type 1 diabetes (T1D) patients with a wide range of disease durations and to healthy adults. Results: The assay showed high linearity and could detect a single copy of unmethylated insulin DNA in experiments using methylated and unmethylated plasmid DNA. The unmethylated insulin DNA level in the type 1 diabetes group, whose β‐cell mass was considerably reduced, was similar to that of healthy adults. An inverse correlation was observed between copy number and disease duration in patients with unmethylated insulin DNA‐positive type 1 diabetes. Conclusions: We developed a novel method for detecting unmethylated insulin DNA in circulation that can be performed using a conventional real‐time PCR system. This method would be useful for analyzing dynamic profiles of β‐cells in human disease such as type 1 diabetes. Abstract : To detect pancreatic beta cell death from the circulating cell‐free DNA. We detect DNA methylation pattern using bisulfite conversion DNA. Also, we can detect one mismatch of DNA sequence very efficiently using amplification‐refractory mutation system PCR with ordinary PCR machine. We have utilized these two techniques together to detect pancreatic beta cell specific sequence in the circulation.